Additive main effects and multiplicative interaction (AMMI) analysis for yield of cassava in Nigeria - Aina, O.O.; Dixon, A.; Akinrinde, E. (Science Alert, 2007)
The problem of genotype-by-environment (G x E) interactions that often complicates the interpretation of multilocational trial analysis making the prediction of genotype performance difficult can be eased with the adoption of the Additive Main Effects and Multiplicative Interaction (AMMI) model analysis. The AMMI model was used in this study to evaluate 20 broad based cassava genotypes established in eight environments in Nigeria in order to; identify stable and adaptable genotypes, determine the magnitude of G x E interaction and identify factors contributing to the G x E interaction pattern. Analysis of variance showed that the effects of environments, genotypes and G x E were highly significant (p< 0.001) for storage root yield. AMMI estimates ranked genotypes differently from unadjusted means producing sharper and more stratified rankings. Genotypes 4(2)1425 and 9102324 was found to be stable and adaptable, 960326 was found to be unstable but high yielding, while 960590 was highly stable but low yielding. Genotypes 960529 and 960860 were specifically adapted to Zaria (Northern guinea savanna) and 960191 was adapted to Ibadan (forest savanna transition zone). High variation in soil moisture availability was identified as a major causal factor of the interaction observed. Ibadan and Mokwa were relatively stable environments but Mallamadori was highly unstable. Mokwa been highly stable could be considered as a good site for selection broad based improved cassava genotypes.